How Should it Be Said: Quipanista, Quipanense or Quipaneño? - Badillo Bramón, Javier (2018)
This study deals with the case of the demonym that is accepted by those from the Villa de Quipán in the Huamantanga district of the Province of Canta, Lima. It explores possible causes of the diferent demonyms assigned to the population of this sector, with focus on linguistic and socio-cultural aspects.